EFEK GANDA PENGELOLAAN WAKAF UANG - Rozalinda Rozalinda (State Islamic University North Sumatra, 2011)
Abstrak: Selama ini pemanfaatan wakaf cenderung tidak produktif dan meng- abaikan kemungkinan potensi untuk kesejahteraan umum. Tulisan ini mendiskusikan perubahan dan implikasi yang timbul dengan dikeluarkannya Undang-undang Nomor 41 tahun 2004 tentang Wakaf. Penulis mengemukakan bahwa wakaf uang dapat ber- peran dalam menunjang proses pembangunan secara menyeluruh, baik pembangunan sumber daya manusia, maupun ekonomi dan sosial. Investasi wakaf uang dapat disalurkan untuk membantu biaya operasional lembaga-lembaga pendidikan, kese- hatan dan sosial. Di sinilah wakaf uang berperan sebagai salah satu sumber pendanaan alternatif untuk peningkatan kesejahteraan umat. Menurut penulis, introduksi Undang- Undang ini menjadi momentum pemberdayaan wakaf secara produktif.Abstract:TheMultiplier Effects of Currency Endowment Management. The employment of wakaf or endowment thus far tends to be unproductive disregarding the possibility of its potential for the public interest. This writing discusses changes and implication brought by the introduction of Regulation No. 41/2004 concerning Wakaf. The author maintains that currency endowment may function to supporting the process of development throroughly, both in human resources and social economy. Currency endowment investment may be distributed as a mean of assisting operational funding of educational, health and social institutions. It is on this that currency endowment plays the role as an alternative financial resource for the betterment of social prosperity. According to the author, the introduction of this regulation would become an avenue for empowering endowment productively.Kata Kunci: wakaf uang, ekonomi umat, UU No. 41/2004